A study of Anti Thyroid Peroxidase (TPO) Antibody Titres in patients seeking treatment at a tertiary health care centre - Shrestha, Prajaya Sikar; Rajouria, Alark Devkota; Malla, Dipak; Bhattarai, Samyukta; Amatya, Bharat Bahadur; Bajracharya, Manil Ratna (Journal of Diabetes and Endocrinology Association of Nepal, 2019)
Background: One of the main cause of thyroid disease is autoimmune thyroid disease and anti thyroid peroxidase (TPO) antibodies is a major marker of the condition. There are very few studies in the country regarding the etiology of thyroid disorders and hence this study is being conducted for it.Methods: This is retrospective cross sectional study from 28 January 2019 to 29 July 2019 done at National Academy of Medical Sciences, Bir Hospital, Kathmandu. The laboratory serum sample data of all Anti TPO antibody results from patients seeking treatment at the instituition were analyzed for age and gender variation. Anti TPO antibody titre of equal or more than 34 IU/ml was considered as positive.Results: Out of 768 samples analysed for study, 79.9% were of women and 20.1 % were of men. A total of 205 (26.7%) were positive for anti TPO antibodies of which 83.4% were women and 16.6% were men . Women had more patients with anti TPO antibodies positive as compared men (27.9 vs 21.1%). Mean Anti TPO titre were also more in women as compared to men (61.01 vs 48.20 IU/ml).Conclusions: About one fourth of the patients had siginificant titers of anti TPO antibodies suggestive of thyroid autoimmunity. Both prevalence of positive anti TPO antibody titres and the mean anti TPO antibody titre values were more in women as compared to men. Further well designed larger community studies are required.